The Method of Probabilistic Forecasting as a Tool of the Psycholinguistic Analysis of a Creolised Text: The Perception of Social Advertising Codes - Gridina, Tatiana A.; Konovalova, Nadezhda I. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2022)
This article verifies the congruence of the verbal and nonverbal codes of social advertising in terms of the expression of the transmitted idea, which makes it possible to adequately restore the lacunarised text (with the slogan excluded while preserving the visual sequence). It is proved that in the process of interpretation of the general idea of the restored advertising slogan, both universal and nationally specific aspects of the verbal embodiment of the perceptual image represented by the nonverbal component are revealed. The authors single out factors contributing to the perception of the meanings of social advertising: the commonality of value presuppositions, the linguo-pragmatic orientation of the advertising text (the significance of information for the addressee), the suggestive nature of the polymodal complex (the emotional power of the visual series and its auditory accompaniment in the form of music and voice in the video advertising). The article characterises strategies for filling text gaps, i.e. stereotypical (using ready-made verbal clichés, including common advertising slogans of a typical syntactic structure) and creative (using word-making innovations, metaphors, figurative comparisons, phraseological precedents, quotes, and figures of expressive syntax). A special aspect of the analysis of the experimental material is the national and cultural specificity of the associative thinking of the respondents: the Russian-speaking participants of the experiment — when perceiving Chinese advertising, and the Chinese participants of the experiment — when translating the content of the restored slogan of Chinese advertising into Russian.